2002
DOI: 10.1001/archinte.162.5.600
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Empirical Management of Acute Cystitis on Unnecessary Antibiotic Use

Abstract: Empirical antibiotic treatment of acute cystitis in women without testing for pyuria promotes unnecessary antibiotic use. A simple decision rule provides for prompt treatment of infected women while reducing antibiotic overuse and unnecessary urine testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 31 publications
2
81
1
3
Order By: Relevance
“…2,3 The rationale of these studies is to provide clinicians with a clinical decision rule to improve the quality of UTI care. 4,5 McIsaac et al have shown that the application of a simple diagnostic algorithm can result in the correct treatment of most females with UTI and can reduce unnecessary urine culture testing and antibiotic prescriptions. 5 Comparable studies of UTI predictors have seldom been performed for male general practice patients.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,3 The rationale of these studies is to provide clinicians with a clinical decision rule to improve the quality of UTI care. 4,5 McIsaac et al have shown that the application of a simple diagnostic algorithm can result in the correct treatment of most females with UTI and can reduce unnecessary urine culture testing and antibiotic prescriptions. 5 Comparable studies of UTI predictors have seldom been performed for male general practice patients.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 McIsaac et al have shown that the application of a simple diagnostic algorithm can result in the correct treatment of most females with UTI and can reduce unnecessary urine culture testing and antibiotic prescriptions. 5 Comparable studies of UTI predictors have seldom been performed for male general practice patients. As a consequence, guidelines for diagnosis and treatment of UTI in males are mainly based on female studies, although one can question whether the generalisation of these criteria to males is valid due to the clear genito-urinary differences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, urine culture remains the definitive diagnostic investigation for acute cystitis and the presence of 10 2 cfu/mL or more of urine indicates active infection. Admittedly, routine urine culture is not always necessary for diagnostic purposes (McIsaac et al 2002). It is considered more cost-effective to manage and treat patients symptomatic of uncomplicated cystitis without an initial urine culture because antimicrobial therapy is often completed before culture results are made available.…”
Section: Laboratory Diagnosismentioning
confidence: 99%